2016
DOI: 10.1111/anae.13644
|View full text |Cite
|
Sign up to set email alerts
|

Potentially modifiable risk factors for atrial fibrillation following lung resection surgery: a retrospective cohort study

Abstract: Atrial fibrillation is the most frequent arrhythmia after thoracic surgery and is associated with increased hospital costs, morbidity and mortality. In this study, we aimed to identify potentially modifiable risk factors for postoperative atrial fibrillation following lung resection surgery and to suggest possible measures to reduce risk. We retrospectively reviewed the medical records of 4731 patients who underwent lobectomy or more major lung resection over a 6-year period. Patients who developed atrial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Alcohol consumption was defined as consuming eight alcohol drinks or more per week for women and 15 or more per week for men. [ 9 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alcohol consumption was defined as consuming eight alcohol drinks or more per week for women and 15 or more per week for men. [ 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, many risk factors were reported to be associated with the development of postoperative AF (POAF) such as older age, male sex, hypertension, obesity, smoking, alcohol consumption, and history of chronic obstructive pulmonary disease (COPD). [ 9 12 ] Furthermore, some surgical procedures are reported to be related to the occurrence of POAF. [ 13 16 ] Muranishi et al reported that mediastinal lymph dissection for patients with early-stage lung cancer is associated with a high risk for the development of POAF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an increasingly popular method used to improve causal inferences when analysing observational data in retrospective studies. For example, propensity score matching was used in two recent retrospective studies published in Anaesthesia , one looking at the effect of prolonged propofol infusion and one investigating potentially modifiable risk factors for atrial fibrillation .…”
Section: Corrective Methodsmentioning
confidence: 99%
“…Since I am only including five clinically relevant variables in my model, does that mean I only have to collect data on 50 patients? This sounds too good to be true, since most retrospective studies (like the ones published in Anaesthesia ) I have seen include hundreds, if not several thousand patients. So how do I really calculate the sample size, and why have these published studies included data on so many patients?…”
Section: Sample Size Required For Power To Equal To 080 As a Functiomentioning
confidence: 95%